2013
DOI: 10.1111/ppa.12156
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication of Acidovorax citrulli in planta during infection of melon seedlings requires the ability to synthesize leucine

Abstract: Acidovorax citrulli causes seedling blight and bacterial fruit blotch (BFB) of cucurbits, a serious disease threat to cucurbit seed and fruit production worldwide. Despite its economic importance, current knowledge on the biology and pathology of A. citrulli is limited. This work studies a mini-Tn5 mutant, MJ22-3, that showed reduced virulence on melon seedlings. The gene disrupted by Tn5 was identified as leuB, which encodes a putative 3-isopropylmalate dehydrogenase, an enzyme that appears to be essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…These data suggest that the roles of amino acids in Xoo virulence are not only nutrient suppliers but also regulatory molecules. Moreover, the data shown in Figure 5 indicate that leucine can regulate diverse pathways, as found in other organisms [10,[19][20][21], suggesting that leucine, as well as other amino acids, may be an important factor in regulating the primary metabolism and pathogenicity of Xoo.…”
Section: Relationship Between Amino Acid Synthesis and Xoo Virulencementioning
confidence: 85%
See 2 more Smart Citations
“…These data suggest that the roles of amino acids in Xoo virulence are not only nutrient suppliers but also regulatory molecules. Moreover, the data shown in Figure 5 indicate that leucine can regulate diverse pathways, as found in other organisms [10,[19][20][21], suggesting that leucine, as well as other amino acids, may be an important factor in regulating the primary metabolism and pathogenicity of Xoo.…”
Section: Relationship Between Amino Acid Synthesis and Xoo Virulencementioning
confidence: 85%
“…As some amino acids can function as nutrients as well as regulatory molecules in higher organisms [18,19], we determined whether they could also regulate pathways involved in Xoo virulence. Because the regulatory role of leucine has been extensively studied in higher plants [9,10] and Xoo ∆leuB has no virulence in rice (Figure 2), we chose this mutant for the subsequent experiments. Although Lrp has been confirmed to be a leucine-response regulator in different bacteria [20][21][22], the lrp mutant does not affect Xoo virulence or growth (Figure 2), suggesting that Lrp-dependent leucine signaling might not be important for Xoo infection and that other pathways might be involved in leucine-dependent signaling.…”
Section: Leucine Regulates Virulence-related Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the increased detoxifying enzyme activity can also contribute to the higher resistance to paraquat and H 2 O 2 . Flagella are important for bacterial colonization and biofilm formation ( Conrad, 2012 ; Bogino et al, 2013 ; Ren et al, 2013 ). Quantitative real-time PCR showed that the gene expression level of fliL and flaB , two flagella-associated genes, was 1.4-fold and 1.8-fold higher in the absence of TetR.…”
Section: Resultsmentioning
confidence: 99%
“…Acidovorax citrulli is the causal agent of bacteria fruit blotch (BFB) in cucurbit plants [ 1 , 2 ]. Since its first outbreak in 1987 [ 3 ], BFB has broadened its host range worldwide, together with the lack of effective management methods, making it a potentially serious threat to the cucurbit industry [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. During the last several decades, the occurrence of this disease has been widely reported, while a number of studies have been carried out for the identification and detection of the bacterial pathogen [ 11 ].…”
Section: Introductionmentioning
confidence: 99%